Intervensi Kategorisasi Sosial dalam Mengurangi Prasangka Terhadap Penyandang Distabilitas di Pendidikan Tinggi Islam - Muhammad Johan Nasrul Huda; Nuristighfari Masri Khaerani (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2024)
Social Categorization Intenvention to Decrease Prejudice Against Students With Disability in  Islamic Higher Education. People with disability have been being suffered to prejudice and discrimination not only social context but aslo happen in education circumstance. Particuarly, prejudice againts students with disability has been theatening social harmony and wellbeing that can impact to life quality. Therefore, this study aimed to investigate the effect of social categorisation training on prejudice reduction towards people with disabilities at Sunan Kalijaga State Islamic University. The intervention involves four dimensions: recategorization, reciprocal differentiation, recategorization, and integration. The intervention was applied a day with 10 participants. Findings demonstrated that the t-test rshowed a significant decrease in prejudice scores from 71.4 to 49.7 (t = 21.13; p = .04), illustrating a positive change in attitudes. Although the sample was limited to a small group and there was no control group, these findings suggest that this approach can strengthen student’s inclusive attitudes. Keywords: Prejudice, disability, Inclusive, intervention